Implementasi Program Sekolah Ramah Anak dalam Membentuk Karakter Anak Usia Dini - Saadatul Kholidiyah; Amala, Nisael (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This research aims to determine the extent to which the implementation of child-friendly school programs has shaped the character of young children. Child-friendly education, especially in early childhood education institutions, provides opportunities for children to develop according to their potential through supporting facilities and infrastructure, learning plans that suit the child's characteristics and developing the child's character. The research was carried out at the RA Sunan Muria Poncokusumo Malang. The research method used is a qualitative method with data mining techniques using interviews, observation and literature study. The results of this research are that by implementing child-friendly school programs at PAUD institutions, positive early childhood characters can be formed, such as independence, discipline, care for the environment, achievement and the ability to appreciate the achievements of students. However, researchers also found several characteristics that need to be further optimized, such as responsibility for one's own waste